Epistemologi Pendidikan Anak Usia Dini dalam Perspektif Islam Kontemporer - Muhtarom; Risa Ismi Septiana; Rahmi Herliza; Heti Marwa; Putri Sari Ayuning; Dina Haryati; Jihan Khairunnisa (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
Early Childhood Education (ECE) occupies a strategic position in the educational system as it serves as the foundation for children’s intellectual, emotional, social, spiritual, and moral development. The rapid advancement of globalization, digitalization, and information technology has created new challenges in preserving Islamic educational values while adapting to contemporary developments. This study aims to analyze the epistemology of early childhood education from a contemporary Islamic perspective, focusing on the construction of knowledge, sources of knowledge, methods of acquiring knowledge, and their relevance to current educational challenges. This research employed a qualitative approach using a library research method. Data were collected through documentation techniques by examining books, scientific articles, and other relevant academic literature. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification. The findings reveal that the epistemology of Islamic early childhood education is constructed through the integration of three primary sources of knowledge: revelation, reason, and empirical experience. These sources collectively shape educational objectives, learning materials, methods, and evaluation processes. The study also indicates that contemporary Islamic thought seeks to integrate religious values with modern scientific developments in order to support holistic child development. Therefore, the epistemology of Islamic early childhood education remains highly relevant in addressing contemporary educational challenges by providing an integrative, holistic, and adaptive framework for developing children’s character, spirituality, and competencet.